Chlamydia (lymphogranuloma venereum) peritonitis in a male patient. Issue 4 (14th April 2021) - Antonik, Magdalena; Ovens, Katie J; Labib, Peter L; Briggs, Christopher D
Abstract : A 49-year-old man presented with a 1-week history of abdominal pain, distension, diarrhoea and fatigue. CT of the abdomen and pelvis revealed peritonitis with no identifiable cause. Diagnostic laparoscopy was performed, which excluded gastrointestinal perforation. Peritoneal fluid tested positive for Chlamydia trachomatis and rectal swabs were positive for C. trachomatis serovars consistent with lymphogranuloma venereum (LGV). Additional blood tests also revealed a diagnosis of syphilis. This is a rare documented case of LGV peritonitis in a male without associated immunodeficiency. The patient recovered well following laparoscopic washout and a course of appropriate antibiotics.